‘Choice’ in women’s abortion decision-making narratives: Introducing a supportability approach - Mavuso, Jabulile Mary-Jane Jace; Chiweshe, Malvern Tatenda; Macleod, Catriona Ida (PINS-Psychology in Society, 2022)
Liberal abortion legislation emphasises pregnant persons’ autonomous choices in abortion decision-making. Within psychological theories, decision-making is understood as largely individual, rational and cognitive, with various factors affecting women’s1 abortion decision-making. In this study, purposively recruited from three sites in South Africa and three sites in Zimbabwe, 25 and 18 women, respectively, participated in narrative interviews which were analysed using thematic analysis and a supportability framework. Participants’ narratives constructed continuation of the pregnancy as a ‘non-option’, abortion emerging as the only solution. Economic resources, gender norms and partnerships, and the undesirability of the pregnancy meant the pregnancy was unsupportable at micro- and macro-levels, and sometimes despite parenting being desired by the women. A supportability framework offers opportunities to understand reproductive decision-making as imbricated in the circumstances of the pregnancy which render it (un)supportable, therefore opening up or closing down particular decisions. This framework enables a necessary shift towards systemic understandings of decision-making, and a possible reduction in abortion-related stigma.